(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Background: Head injuries are the most serious injuries in the term of morbidity and mortality. This study was conducted in M.G.M. Medical College, Indore, mortuary among the 200 post mortem cases of road traffic accident victims over the period of one year from 1st October 2014 to 30th September 2015. Objective: To find out demographic profile in fatal road traffic accident victims.